Practices and Outcomes of Participative Management in Japanese Subsidiary Companies in Malaysia. - Saludin, Mohamad Nasir (2005)
This study explores the link between participative management practices (PMP) and participative management outcomes (PMO) in Japanese Subsidiary Companies in Malaysia. One hundred and forty managers from 140 Japanese Subsidiary Companies in Malaysia had completed the questionnaires covering participative management practice (PMP) and four participative management practices outcomes (readiness to accept change, productivity, teamwork effectiveness and customer service quality). Descriptive statistics were used to describe the profile of the subjects in this study and the nature of participative-management-practice programmes. The research utilised F-test (analysis of variance), factor analysis, correlation analysis, and multiple regression analysis to analyse the data.The research found that 65.7 percent of the respondents indicated that the level of participative management practices in the studied Japanese Subsidiary Companies in Malaysia was at medium level. With regard to the type of participative-management-practice programmes, the result indicated that programmes, such as total quality management (TQM), quality control circles (QCC), suggestion scheme and small group activity (SGA) were more frequently practiced in these companies, while, the discussion group, team working, matrix/project management and task forces programmes were regularly practiced in these companies. The other programmes such as morning prayer, company magazine, video presentation and collective bargaining, were less regularly practiced in these companies. From the factor analysis, five factors; consisting of organizational culture, organizational climate, employee empowerment, total employee involvement and leadership; were identified as elements of participative management practices in this study. Statistically significant relationships were found between participative management practices and readiness to accept change, productivity, teamwork effectiveness, and customer service quality. These findings indicate that participative management practices tend to increase productivity, readiness to accept change, customer service quality and teamwork effectiveness. The influence of participative management practices on the participative management outcomes is a clear signal to managers to realize the importance and effectiveness of participative management practices. Overall, this study found that the participative management practices were correlated with the selected participative management outcomes in Japanese Subsidiary Companies in Malaysia. It is recommended that the participative management practices in Japanese Subsidiary Companies be adopted by local firm in Malaysia